1960
DOI: 10.1111/j.1744-6570.1960.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

ABSENCE and EMPLOYEE FEELINGS ABOUT FAIR TREATMENT1

Abstract: Summary This study calls into question again a frequently made assumption that variations in employee absence rates may be accounted for solely by examining the direct rewards and punishments provided by the work situation. Absences among nonsupervisory men at an oil refinery were found to be related to feelings of fair treatment with regard to promotion, irrespective of how good employees see their actual chances for promotion to be. Attitudes concerning the fairness of pay also were found to affect absences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1962
1962
1999
1999

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 2 publications
0
24
0
1
Order By: Relevance
“…Most studies on this topic have focussed upon interpersonal pay comparisons (Dittrich & Carrell, 1979;Hendrix & Spencer, 1989;Patchen, 1960): individuals appear to be absent more often, the more underpaid they feel compared to their colleagues. Research by Oldham et al (1986) has failed to show a relationship between pay inequity and absenteeism.…”
Section: Social Comparison Of Job Outcomesmentioning
confidence: 99%
“…Most studies on this topic have focussed upon interpersonal pay comparisons (Dittrich & Carrell, 1979;Hendrix & Spencer, 1989;Patchen, 1960): individuals appear to be absent more often, the more underpaid they feel compared to their colleagues. Research by Oldham et al (1986) has failed to show a relationship between pay inequity and absenteeism.…”
Section: Social Comparison Of Job Outcomesmentioning
confidence: 99%
“…Specifically, three studies among various work samples found an inverse relationship between pay satisfaction or perceived pay equity and absenteeism ( Patchen , 1960;Dittrich ~ Carrell, 1976;Smith, 1977), while six other studies did not find such a relationship ( Hackman L awler, 1971;Newman, 1974;Lundquist, 1958; Garrison ~ Muchinsky, 1977; . Three other studies found mixed results (Waters ~ Roach, 1971Metzner M ann , 1953).…”
Section: Pressures To Attendmentioning
confidence: 99%
“…Investigating size as a moderator variable, Vroom & Mann (172) found that employees in small groups showed more positive attitudes toward equalitarian leaders (low scores on the F Scale), whereas those in large groups which afforded only limited opportunity for interaction showed more positive attitudes toward authori tarian leaders (high F-Scale scorers). Patchen (126) showed that absentee ism rates were related to employee perceptions of the fairness of company policies rather than to objective measures of pay level, length of time since last promotion, etc. England (37) obtained only c h ance relationships be tween objective measures of attitudes toward company and union among two groups of union members, thereby casting serious doubt upon the validity of previous results inferring, from subjective attitude measures such as interviews, the existence of dual allegiance.…”
Section: Compensationmentioning
confidence: 98%